PERAN KEPEMILIKAN MANAJERIAL SEBAGAI VARIABEL MODERASI ANTARA FINANCIAL DISTRESS, PROFITABILITAS DAN CORPORATE SOCIAL RESPOSIBILITY (CSR) TERHADAP MANAJEMEN LABA - Cahyani, Regina; Hasanah, Nuramalia; Handarini, Dwi (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2025)
This study aims to examine and analyze the impact of financial distress disclosure, profitability, and corporate social responsibility (CSR) on firm value, as well as to investigate the role of managerial ownership in moderating these relationships. This research uses a quantitative method with secondary data in the form of annual and sustainability reports from property and real estate companies listed on the Indonesia Stock Exchange (IDX) for the period 2021 - 2023, with a total of 22 samples and 66 data observations. The analysis used in this study includes descriptive statistical analysis, panel data regression analysis, and moderated regression analysis (MRA) with the help of Eviews 13 software. The research results indicate that financial distress and profitability significantly affect earnings management, while CSR has no effect. In addition, managerial ownership does not moderate the relationship between financial distress, profitability, and CSR on earnings management. These findings suggest that companies tend to manipulate earnings to maintain a positive image, while managerial ownership is not always effective in reducing agency conflicts during financial difficulties. This study provides insights for investors and managers in understanding the factors that influence earnings management practices. Keywords: earnings management, financial distress, profitability, corporate social responsibility, managerial ownership.